Pengaruh Islam Kultural terhadap Perkembangan Seni dan Arsitektur di Nusantara - Irfan Padlian Syah; Muthia Zahra; Iffan Ahmad Gufron; Masykur (Ta’wiluna: Jurnal Ilmu Al-Qur'an, Tafsir dan Pemikiran Islam, 2026)
This study examines the process of Islamic acculturation in the arts and architecture of Nusantara society through a qualitative approach based on library research, employing qualitative content analysis and historical hermeneutics. The primary objective of this study is to uncover the patterns of Islamic acculturation within Nusantara culture while tracing Islamic values as reflected in local arts and architecture. The findings indicate that the Islamization process in Nusantara occurred through an additive pattern of acculturation rather than one of complete replacement. Islam did not eradicate the deeply rooted Hindu-Buddhist traditions; instead, it engaged in a prolonged and dynamic process of cultural negotiation and synthesis. This is evident in three primary aspects: the development of Arabic calligraphy, which transformed into Pegon and Jawi scripts as well as locally styled gravestone ornamentation; the utilization of wayang kulit as a medium of Islamic proselytization through the incorporation of Islamic values; and the architectural form of mosques that adopted local elements such as the tiered roof (atap tumpang) and the bedug drum within an Islamic functional framework. In the institutional context, mosques during the early period of Islamic development in Nusantara functioned as comprehensive institutions encompassing spiritual, educational, social, and political dimensions. However, with the advancement of modernization, these functions gradually narrowed in scope. This study affirms that Islam in Nusantara represents the product of an active civilizational creativity, shaped through a dialogue between the universal teachings of Islam and local wisdom, rather than a mere cultural adoption from the Middle East.